Proses Transformasi Pengetahuan Budaya Songket pada Masyarakat Pandai Sikek - Elfitri Kurnia Erza; Pawit M Yusup; Wina Erwina (Majalah Sainstekes, 2017)
Information development has prompted a transition within society, which has changed from local society to information society. The transition appears accordingly in the process of knowledge sharing of “Songket” waving technic in Pandai Sikek. This social phenomenon necessarily affects local knowledge of the community and initiates some knowledge transformation. The aim of this paper is to see how exactly the transformation of the local knowledge of “Songket” waving technic as a part of society’s culture arise.  The paper employs qualitative methods combined with ethnographical approach. Data are collected through observation, in depth interview, and documentation studies. Conducted research shows that the cultural knowledge regarding Songket has altered from a belief system to a social factor of the society involved.